Effect of relative humidity on SOA formation from isoprene/NO photooxidation: enhancement of 2-methylglyceric acid and its corresponding oligoesters under dry conditions - Zhang, H.; Surratt, J. D.; Lin, Y. H.; Bapat, J.; Kamens, R. M. (Atmospheric chemistry and physics, 2011)
The effect of relative humidity (RH) on secondary organic aerosol (SOA) formation from the photooxidation of isoprene under initially high nitric oxide (NO) conditions (i.e., isoprene/NO ~3) was investigated in a dual outdoor smog chamber. Based upon particle volume concentration measurements and the detailed chemical characterization of isoprene SOA using gas chromatography/mass spectrometry (GC/MS) and ultra performance liquid chromatography/electrospray ionization high-resolution quadrupole time-of-flight mass spectrometry (UPLC/ESI-HR-Q-TOFMS), enhanced SOA formation was observed under lower RH conditions (15–40 %) compared to higher RH conditions (40–90 %). 2-methylglyceric acid (2-MG) and its corresponding oligoesters, which have been previously shown to form from further oxidation of methacryloylperoxynitrate (MPAN), were enhanced in the particle-phase under lower RH conditions. In addition, an abundant unknown SOA tracer likely derived from the further oxidation of MPAN was detected and enhanced under lower RH conditions. In contrast, the 2-methyltetrols, which are known to mainly form from the reactive uptake of isoprene epoxydiols (IEPOX) under low-NO conditions in the presence of acidified aerosol, did not substantially vary under different RH conditions; however, isoprene-derived organosulfates were found to be enhanced under high-RH conditions, indicating the likely importance of the aqueous aerosol phase in their formation. Based upon the detailed chemical characterization results, particle-phase organic esterification is tentatively proposed to explain the observed enhancements of isoprene SOA mass under lower RH conditions. Alternative mechanisms explaining the enhancement of 2-MG and its corresponding oligoesters cannot be completely ruled out. This is one of only a few chamber studies that have examined the effect of RH on isoprene SOA formation. In comparison to our recent results obtained from aromatic SOA formation, the effect of RH on isoprene SOA formation is reversed. The results of this study highlight the importance of elucidating the key reactive intermediates that lead to SOA formation, especially since RH likely affects their ability in forming SOA. Furthermore, ignoring the effects of RH may significantly affect the accuracy of both regional and global SOA models.